2010
DOI: 10.1515/hf.2010.036
|View full text |Cite
|
Sign up to set email alerts
|

A study of water exchange in wood by means of 2D NMR relaxation correlation and exchange

Abstract: Two-dimensional T 1 -T 2 1 H NMR relaxation correlation spectra and T 2 -T 2 relaxation exchange spectra for samples of spruce wood across the full moisture content range from 0% to )100% are presented. The T 1 -T 2 spectra unambiguously identify water in different environments within the wood that overlap in the corresponding and more traditional one-dimensional T 1 or T 2 experiment. The T 2 -T 2 spectra unambiguously reveal the presence of water exchange between the lumen and cell wall above the fibre satur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
82
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(86 citation statements)
references
References 29 publications
3
82
1
Order By: Relevance
“…A comparison of void geometries and volumes shows good correspondence between pore volumes of pits and lumina and the areas of respective T 2 peaks assigned to these voids for water-saturated samples (Fredriksson and Thygesen 2017). Even more details about the chemical environment of water in pores within wood can be gained from T 1 to T 2 2D LFNMR correlation spectroscopy as reported by Cox et al (2010). In this method, T 1 and T 2 relaxations are determined simultaneously allowing an analysis of their correlation (Song 2009;Song et al 2002).…”
Section: Spectroscopic Techniquesmentioning
confidence: 91%
See 1 more Smart Citation
“…A comparison of void geometries and volumes shows good correspondence between pore volumes of pits and lumina and the areas of respective T 2 peaks assigned to these voids for water-saturated samples (Fredriksson and Thygesen 2017). Even more details about the chemical environment of water in pores within wood can be gained from T 1 to T 2 2D LFNMR correlation spectroscopy as reported by Cox et al (2010). In this method, T 1 and T 2 relaxations are determined simultaneously allowing an analysis of their correlation (Song 2009;Song et al 2002).…”
Section: Spectroscopic Techniquesmentioning
confidence: 91%
“…In particular, CPMG is a commonly used sequence for determining T 2 relaxation as it reduces effects of magnet inhomogeneity by multiple refocusing of the spins in the transverse plane. Several studies have employed LFNMR for characterising water in both untreated Araujo et al 1992Araujo et al , 1994Cox et al 2010;Flibotte et al 1990;Fredriksson and Thygesen 2017;Labbé et al 2002Labbé et al , 2006Menon et al 1987;Passarini et al 2015;Telkki et al 2013;Elder 2008, 2009) and modified wood (Elder et al 2006;Hietala et al 2002;Javed et al 2015;Kekkonen et al 2014;Elder 2008, 2009). Based on a deconvolution of the decay curves, signals from water in different compartments within the wood structure have been analysed Araujo et al 1992Araujo et al , 1993Fredriksson and Thygesen 2017;Passarini et al 2015) (see Fig.…”
Section: Spectroscopic Techniquesmentioning
confidence: 99%
“…In the light of the recent results by Zelinka et al (2012), these two states of water cannot be interpreted as freezing and non-freezing bound water, respectively. Perhaps the two types of water found by Cox et al (2010) correspond to water bound to the two different accessible sides of cellulosic microfibrils identified by Bergenstråhle et al (2008), as these were also found to have different spin-lattice relaxation times. However, that water bound to two different sides of cellulose aggregates should be separable while water bound to hemicelluloses or lignin should blend into these two populations and not stand out does on the other hand seem peculiar.…”
Section: States Of Water In Woodmentioning
confidence: 98%
“…According to Araujo et al (1994), cell wall water diffuses so fast that chemical exchange between different bonding states (if they exist) evens out any differences in relaxation times and results in a single population being found for cell wall water. Employing a more advanced 2D T 1 -T 2 LFNMR experiment, Cox et al (2010) were able to identify two different states of water within the wood cell wall. These two components had similar spin-spin relaxation times (thus resulting in only one CPMG population), but different spin-lattice relaxation times.…”
Section: States Of Water In Woodmentioning
confidence: 99%
“…The description of simple spin-1/2 systems can be accomplished by means of longitudinal (T1, or spin-lattice) and transversal (T2, or spin-spin) relaxation times; the values depend on the spin interactions and the geometry of molecular motion. T1 and T2 change in comparison to the reference systems, which give solid information about materials' structural properties and modifications [43].…”
Section: Digital Speckle Correlation (Dsc)mentioning
confidence: 99%